Applications of GIS and remote sensing in the hydrological study of the Upper Bernam River Basin, Malaysia - Lai, Sai Hin, Dr.; Mohd Amin, Mohd Soom, Prof. Dr.; Law, Puong Ling, Assoc. Prof. Dr.; Mah, Darrien Yau Seng (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/